2015
DOI: 10.1002/aelm.201400002
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Morphologic Influence of WO3 Nanoparticles on the Electrochromic Performance of Dual‐Phase a‐WO3/WO3 Inkjet Printed Films

Abstract: The optimization of tungsten trioxide (WO3) nanoparticles produced via hydrothermal synthesis for application in electrochromic (EC) devices is reported. The structure and morphology of the nanoparticles are controlled by changing the acidity of the aqueous solvent added to the sol‐gel precursor (peroxopolytungstic acid) during synthesis. Orthorhombic hydrated WO3 nanorods or monoclinic WO3 nanoslabs are obtained when HCl is added, while synthesis only in aqueous medium results in a mixture of both types of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…[35][36][37] Recent reports of Azam et al, [35] showed for EC device based on 2D WO 3 nanosheets an optical modulation of 62.57% during +3 V (bleached state) and −3 V (colored state) and a color-switching response-time of 6.97 s for bleaching and 10.74 s for coloration, whereas Huo et al, [36] observed for devices based on hexagonal/amorphous WO 3 core/shell nanorod arrays an optical modulation of 67.7%, and response times of 15 s for coloring and 21 s for bleaching (±3 V), outperforming performances of ECDs based on pure hexagonal WO 3 nanorods. [35][36][37] Recent reports of Azam et al, [35] showed for EC device based on 2D WO 3 nanosheets an optical modulation of 62.57% during +3 V (bleached state) and −3 V (colored state) and a color-switching response-time of 6.97 s for bleaching and 10.74 s for coloration, whereas Huo et al, [36] observed for devices based on hexagonal/amorphous WO 3 core/shell nanorod arrays an optical modulation of 67.7%, and response times of 15 s for coloring and 21 s for bleaching (±3 V), outperforming performances of ECDs based on pure hexagonal WO 3 nanorods.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[35][36][37] Recent reports of Azam et al, [35] showed for EC device based on 2D WO 3 nanosheets an optical modulation of 62.57% during +3 V (bleached state) and −3 V (colored state) and a color-switching response-time of 6.97 s for bleaching and 10.74 s for coloration, whereas Huo et al, [36] observed for devices based on hexagonal/amorphous WO 3 core/shell nanorod arrays an optical modulation of 67.7%, and response times of 15 s for coloring and 21 s for bleaching (±3 V), outperforming performances of ECDs based on pure hexagonal WO 3 nanorods. [35][36][37] Recent reports of Azam et al, [35] showed for EC device based on 2D WO 3 nanosheets an optical modulation of 62.57% during +3 V (bleached state) and −3 V (colored state) and a color-switching response-time of 6.97 s for bleaching and 10.74 s for coloration, whereas Huo et al, [36] observed for devices based on hexagonal/amorphous WO 3 core/shell nanorod arrays an optical modulation of 67.7%, and response times of 15 s for coloring and 21 s for bleaching (±3 V), outperforming performances of ECDs based on pure hexagonal WO 3 nanorods.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…However, due to the difficulty in determining local disorder, there is still no well-established electronic localization mechanisms for aTMOs. Unveiling atomic short-range order is thus crucial to understand optical and electronic processes in aTMOs and would also be of vital importance in nanoparticle systems where the high-surface-to-bulk ratio results in lower crystallinity arising from structural reconstruction and surface disorder 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we evaluated the stability of the films by the capacity loss, which was calculated the charge densities difference between the first CV cycle and the following cycles. 34 And the charge densities were the summation of Qc and Qa. As shown in Figure 5, the capacity of GVM film and VM film decrease slightly compared with GV film and V film, respectively, which leads to a better cyclic stability of these films.…”
Section: Resultsmentioning
confidence: 99%